If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y in (-oo:+oo)
(2/3)*y-((7/4)*y) = -13 // + 13
(2/3)*y-((7/4)*y)+13 = 0
(2/3)*y+(-7/4)*y+13 = 0
13-13/12*y = 0 // - 13
-13/12*y = -13 // : -13/12
y = -13/(-13/12)
y = 12
y = 12
| -2x^2+12x=-36 | | 5y-1=3(y+3) | | 1-5x=4x+16 | | 3xsquared-10x=-1 | | 33c=726 | | 2(-4p-1)+(2.5-p)=x | | 5/2t-10=-30 | | 10x+30-20=90 | | 3.2b=1.8+3.6b | | f(x)=2x^3-8x^2+4x-16 | | 5y-2=28y | | 2b+42=7a+33 | | .25(r+8)=r-8 | | 4x+7x-4=56 | | 3x+12=-112 | | 4x+2=3x-16 | | s=2ab | | 4x+10+2x-20=90 | | 7(x-3)=3x+4x | | b^2-16b+70=0 | | 7b^2-b-6=0 | | x^2+y^2+19x-4y=0 | | 53+4b=11+2b | | b-28.2=5.7 | | 2t-11t= | | (5x-6)(x+1)= | | m/4-m | | 5a-1=19 | | -x-5(-7x+16)=22 | | 7t-30+t^2=0 | | 91000=35x^2-3640x+7000 | | 15+5x=-75 |